Kemampuan Pedagogical Content Knowledge (PCK) Guru Ipa Kelas VIII Smp Negeri Se-Kabupaten Sukoharjo Dalam Menyusun RPP Kurikulum 2013 Tahun Ajaran 2016/2017 - KASTUTIK, Anita Windi; , Dra. Hariyatmi, M.Si (2017)
Teacher is one of the critical success factors of the learning process. The purpose of this study was to determine the PCK capability of science teachers at eighth grade junior high school in Sukoharjo. The research is a qualitative descriptive. The population in this study is fifteen teacher science eighth junior high school class in Sukoharjo. The sample in this study consisted of ten teachers from five schools that have used the 2013 curriculum. Sampling technique in this research is purposive sampling and random sampling, every teacher taken five lesson plan. Based on the research that has been done shows that the CK capability of teachers includes enough (51.6%), PK ability is good (78.7%), and the ability of PCK categorized as good (69.1%), so, the ability of PCK capability of science teachers eighth grade junior high school in sukoharjo in arranging the lesson plan the 2013 curiculum 2016/2017 academic year including good